Analysis Of Head Length Effect Of Wire Rope Sensor On Output Voltage - Harun, Noor Hasmiza (2008)

(untitled)
Wire rope are used extensively in industrial applications involving lifting machines such as lift system, cable car system as well as crane services. In many cases, failure of a wire rope could lead to expensive damage to equipment or even to loss of life. Structural integrity of the wire rope is to be monitored to safe guard human lives. Regular periodic inspection is necessary for optimum safe utilization. Apart from visual inspection, the non destructive test methods are available to check the condition of this wire rope. Various methods have been used for wire rope testing such as eddy current, ultrasonic and radiographic. However, each method has some drawbacks in their application. Currently, there is no specific tool to design the wire rope sensor. Trial and error method was used to design the wire rope sensor and it will consume longer time for prototyping and fabricating the sensor. This method does not offer rapid performance evaluation of the designed sensor and it will cause the process of improving the efficiency of the sensor will be slower. Therefore, development of a model to design the wire rope sensor has been proposed. This model is able to investigate variable parameter involved in designing the wire rope sensor and it will speeding the process of prototyping the wire rope sensor. In this research, a fabricated wire rope sensor based on electromagnetism principles has been analyzed. The sensor applies the theory of magnetic circuit for the crack detection operation. This is an added feature to the sensor as the magnetic circuit does not need any energy supply to be energized which indirectly reduces its energy consumption. This sensor is a passive type sensor and its structure is very simple. It is made up of three main components; sensor head, center yoke rounded with copper wire and a set of permanent magnet. The sensor will only produce a signal when there is a relative movement between the sensor head and the tested wire rope. Derivations of theoretical calculations using permeance method was done to obtain a tools that manages to study the physical structures behaviors of the sensor. Finite Element Method (FEM) simulations and laboratory experiments have been conducted to observe the effects of head length to the output voltage of the sensor. The objective of this research is to perform the analysis of head length, Lh effect of wire rope sensor on output voltage was successfully achieved. A theoretical equation for the voltage induced by the sensor has been deduced using permeance method. Finite Element Method (FEM) simulation and laboratory experiments were done to observe the effects of head length of the sensor head to the output voltage of the sensor. Comparison between simulation result, theoretical calculation and laboratory experiment shows almost identical results. The analysis is necessary to obtain the best design for the wire rope sensor that would produce high output voltage.